The Positivistic Paradigm Relevant in Research Rural Sociology - Irwan Irwan (Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The scientific research in sociology has several paradigms namely positivistic, social constructivism, advocacy, participatory and pragmatic paradigm (Creswell, 2010). Positivistic paradigm considers the social reality that occurs as empirical, observed clearly and can be proven scientifically. In order to study the phenomenon in society that the positivistic paradigm has great contribution. Therefore, a question arises whether the positivistic paradigm has a major influence on the study of society? is it relevant that the positivistic paradigm used in rural sociology research? The positivistic paradigm of social phenomena is understood from an outside perspective based on the understanding of established theories. The Social reality is a phenomenon whose existence is determined by other social phenomena (interrelated variables) and its existence can be described into symbols that have been established in society. The problems in society in particular can not only be explained in constructivist paradigm but there is social phenomenon which surely needs to be explained in other paradigm such as positivistic paradigm. The positivistic paradigm is in the position of answering the problem of seeing the level and influence of social reality. Therefore, the positivistic paradigm is highly relevant to the study of rural sociology, where the phenomena occurring is unlimited and to simplify social phenomena, therefore statistics analysis is needed as a basis for concluding the data obtained from the field. In rural sociological studies, various social phenomena are associated with stratification, education, status, religion and so on. To answer the problems that occur in rural communities need a positivistic paradigm.